Spatial Analysis of Accident Rates to Determine Accident-Prone Areas on the Waena–Sentani Road, Jayapura Regency - Erwin, Erwin (Westscience Press, 2024)
The number of traffic accidents in Indonesia is still relatively high, based on data from the Jayapura Regency Traffic Unit, the number of traffic accidents in Jayapura Regency from 2017 to 2019 was 360 incidents. Jayapura Regency which is one of the regencies in Papua Province that is directly related to Jayapura City which continues to experience economic growth and population growth of 2.50% per year (BPS. Jayapura Regency in figures, 2020), thus causing quite high population activity and mobility. The method used in determining blacksite and blackspot areas is the Equivalent Accident Number method, Upper Control Limit and Upper Control Limit to determine the location of the blacksite and the Cumulative Summery (Cusum) method to determine the location of blackspots on Jalan Raya Waena Sentani. Accident-prone areas on the Waena-Sentani Road are located in areas one and area four. Region one with an Accident Number Equivalent value of 155, an Upper Control Limit value of 143.5, and an Upper Control Limit value of 144. Region four with an Accident Number Equivalent value of 155, an Upper Control Limit value of 144.2, and an Upper Control Limit value of 153. with the highest cusum value at location one of 2.56 and location two of 3.34.